Analisis Mutu Rekam Medis Kasus Bedah Dengan Metode Kualitatif Di Rsud Dr R Goeteng Taroenadibrata Purbalingga - Sholikhah, Nur Amalia; Sri Sugiarsi; Astri Sri Wariyanti (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2024)
The quality of medical records can be seen from 3 criteria for completeness of content, accuracy, timeliness and fulfillment of legal aspects. Medical record quality analysis is carried out in two ways, namely quantitative analysis and qualitative analysis. The purpose of this study was to analyze the quality of medical records of surgical patients with qualitative methods at RSUD dr R Goeteng Taroenadibrata Purbalingga. This type of research is a mix method. The object population was 204 surgical case medical records and the subject population was 2 general surgeons and 4 nurses, object sampling using the Slovin formula with e = 0.1 resulted in 67 files while subject sampling used purposive sampling. How to collect data by observation using Checklist and Unstructured Interviewdata processing techniques include 2 methods, namely Quantitative and Qualitative. The results of this study found that for consistency of diagnostic recording 57 (84%) files were consistent while 11 (14%) files were inconsistent. The consistency of recording medical record documents as much as 54 (80%) is consistent and 14 (20%) is inconsistent. The consistency of recording things done during treatment and treatment was 45 (66%) consistent and 23 (34%) inconsistent. The consistency of recording informed consent as much as 65 (95%) is consistent and 3(5%) is inconsistent. The analysis that could potentially lead to damages was 67 (99%) consistent and 1 (1%) inconsistent. Factors causing the inconsistency of medical record recording include man, material, machine, method factors.